Treatment of Placenta Increta With High-Intensity Focused Ultrasound Ablation and Leaving the Placenta in situ: A Multicenter Comparative Study - Guan, Xiaoping; Huang, Xiaoqin; Ye, Min; Huang, Guohua; Xiao, Xiao; Chen, Jinyun (Frontiers in Medicine, 2022)
Objective: To explore the feasibility of simple high-intensity focused ultrasound (HIFU) ablation for placenta increta. Methods: Ninety-five patients after a vaginal delivery were enrolled in this retrospective cohort study, 53 patients were treated with simple HIFU ablation, and 42 patients were treated with HIFU followed by uterine curettage. Results: All 95 patients were successfully treated with a single-session HIFU procedure, and in the control group, the necrotic placental tissue was removed with curettage. Vaginal hemorrhage did not occur in either group. The duration of bloody lochia was 25.9±8.6 days in the sHIFU group and 24.2±8.8 days in the control group (P > 0.05). The median serum HCG level was 3222 mIU/mL and 2838 mIU/mL in the sHIFU and control groups, respectively, which decreased and returned to normal within 30 days, and the differences were not significantly on comparing the blood HCG level in the two groups at 7, 15, and 30 days after HIFU (all P > 0.05). Decreased menstrual volume occurred in 85.71% of patients in the control group, which was higher than that in the sHIFU group (23.08%) ((2=6.839, P＜0.001). During 2-8 years of follow-up, 6 pregnancies occurred in the sHIFU group without any recurrence of placenta increta, 3 pregnancies occurred in the control group and 1 patient developed a repeat placenta increta. Conclusions Simple HIFU treatment is safe and effective for postpartum placenta increta and leaving the placenta in situ. It is a promising option for patients who wish to preserve their fertility and conceive.